Responses of Fungi Maggot (Bradysia impatiens Johannsen) to Allyl Isothiocyanate and High CO2 - Gou, Yu-Ping; Quandahor, Peter; Mao, Liang; Li, Chun-Chun; Zhou, Jing-Jiang; Liu, Chang-Zhong (Frontiers in Physiology, 2022)
Botanical pesticide is highly recommended for Integrated Pest Management (IPM), due to its merits of environmental friendliness, safe to non-target organisms, operators, animals and food consumers. The experiment was conducted to determine the lethal and sublethal effects of Allyl isothiocyanate (AITC) on eggs, 3rd instar larvae, pupae, females and males of Bradysia impatiens Johannsen (B. impatiens). Different concentrations of AITC under ambient CO2 by conical flask sealed fumigation method was conducted. The results showed that there was a significant linear relationship between different concentrations of AITC and the toxicity regression equation of B. impatiens. The sublethal concentrations of AITC had significant effects on the larval stage, pupal stage, pupation rate, pupal weight, adult emergence rate and oviposition. The pupation rate, pupal weight, and adult emergency rate were significantly (P< 0.05) affected by AITC fumigation. Pupation rate was the lowest after fumigation treatment of AITC at LC50 (36.67%), followed by LC25 (41.94%), compared with the CK (81.39%). Female longevity was significantly (P< 0.05) shortened by fumigation at LC25 (1.75 d) and LC50 (1.64 d), compared with CK (2.94 d). Male longevity was shorter at LC25 (1.56 d) than at LC50 (1.25 d), and had no significant difference between those two treatments. The fumigation efficiency of AITC was significantly increased under high CO2 condition. Furthermore, detoxification enzyme activities and antioxidant enzyme activities were accumulated under high CO2 condition. The fumigation method in the application of AITC can be useful in areas where B. impatiens is a major concern.